ANTIBIOTIC RESISTANCE AND VIRULENCE PROPERTIES IN ESCHERICHIA COLI STRAINS FROM CASES OF URINARY TRACT INFECTIONS - Olorunmola, Felix Oluwasola; Kolawole, Deboye; Lamikanra, Adebayo (African Journal of Infectious Diseases (AJID), 2013)
This study determined E. coli resistance to commonly used antibiotics together with their virulence properties in Ile-Ife, Nigeria. A total of 137 E. coli isolates from cases of urinary tract infection were tested for their sensitivity to commonly used antibiotics and possession of virulence factors using standard methods. Their ability to transfer resistance was also determined. The isolates demonstrated a high and widespread resistance (51.1 % to 94.3 %) to all the antibiotics used except Nitrofurantoin (7.3 %). A total of 50 (36.5 %) of the isolates were resistant to 10 of the eleven antibiotics employed. Sixty three per cent (63 %) of the 107 trimethoprim resistant E. coli transferred their resistances while amoxicillin, gentamycin, augmentin, tetracycline and erythromycin were co-transferred with trimethoprim. Fifty one (37.2 %) of these multi-resistant isolates possessed one or more virulent factors. The study concluded that urinary tract infection due to E. coli in Ile-Ife may be difficult to treat empirically except with nitrofurantoin, due to high resistance to commonly used antibiotics. It is imperative that culture and susceptibility tests be carried out on infecting pathogen prior to treatment, in order to avoid treatment failure and reduce selective pressure that could result in the spread of uropathogenic E. coli in the environment.